Pengaruh Implementasi E-Filling dan Literasi Digital Terhadap Kepatuhan Wajib Pajak UMK di Kabupaten Karanganyar - Dyah Ayu Nugraheni; Fadjar Harimurti (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The study addresses literacy regarding MSME taxpayer compliance within Karanganyar Regency. The formulated hypothesis proposes that the implementation of e-filing and the existence of digital literacy exert a positive contribution toward MSME taxpayer compliance in Karanganyar Regency. The sampling technique applied was the accidental sampling approach, in which participants were chosen based on MSME actors who happened to be encountered by the investigator during fieldwork. The research data were gathered through questionnaires administered to MSME actors across Karanganyar Regency. The kind of information employed in this investigation was categorized as primary data. Analytical results indicated that the implementation of e-filing does not produce a notable effect simultaneously on MSME taxpayer compliance in Karanganyar Regency. Further outcomes revealed that digital literacy also shows no significant simultaneous impact on MSME taxpayer compliance in Karanganyar Regency. Findings from the F-test demonstrated an insignificant influence of combined e-filing implementation and digital literacy on MSME taxpayer compliance in Karanganyar Regency. The calculation provided an R² value of 0.002, equivalent to 2%, signifying that only a minimal effect is contributed by the implementation of e-filing and digital literacy toward MSME taxpayer compliance in Karanganyar Regency